Organizational Culture, Government Regulations and Corporate Competitveness of Merged Deposit Money Banks in Nigeria (Global Journal of Management and Business Research, 2019)
The Nigerian banking sector is germane to the growth of the nation's economy and several reforms over the years have orchestrated merger and acquisition. The marriage of convenience occasioned by the banking consolidation exercise of 2005 by the Central Bank of Nigeria (CBN) led to dilution of ownership and fusing together banks with different goals, objectives and ideology. These have led to rebranding, cultural disharmony, and uncompetitive behaviours which were considered not suitable for the new direction. Cross-sectional research design was adopted and primary data collated. The research instrument was validated and reliability was carried out using the Cronbach alpha analysis. A sample size of four hundred and seventy three (473) was determined using Roasoft sample size calculator. The result revealed that organizational culture significantly affected the corporate competitiveness of the surveyed banks. The study variables organizational culture (B =0.929, R2 = 0.619, p < 0.05, F(1,455) = 738.509), government regulations (B =0.710, R2 = 0.691, p < 0.05, F(1,454) = 106.413).
Keywords: organizational culture; government regulations; corporate competitiveness; merged money deposit banks; central bank of nigeria